“Endothelial Antibody Factory” at the Blood Brain Barrier: Novel Approach to Therapy of Neurodegenerative Diseases - Reynald Thinard; Attila E. Farkas; Marta Halasa; Melanie Chevalier; Klaudia Brodaczewska; Aleksandra Majewska; Robert Zdanowski; Maria Paprocka; Joanna Rossowska; Lam Tri Duc; Ruth Greferath; Istvan Krizbai; et al. (Pharmaceutics, 2022)
The failures of anti-β-amyloid immunotherapies suggested that the very low fraction of injected antibodies reaching the brain parenchyma due to the filtering effect of the BBB may be a reason for the lack of therapeutic effect. However, there is no treatment, as yet, for the amyotrophic lateral sclerosis (ALS) despite substantial evidence existing of the involvement of TDP-43 protein in the evolution of ALS. To circumvent this filtering effect, we have developed a novel approach to facilitate the penetration of antibody fragments (Fabs) into the brain parenchyma. Leveraging the homing properties of endothelial progenitor cells (EPCs), we transfected, ex vivo, such cells with vectors encoding anti-β-amyloid and anti-TDP43 Fabs turning them into an “antibody fragment factory”. When injected these cells integrate into the BBB, where they secrete anti-TDP43 Fabs. The results showed the formation of tight junctions between the injected engineered EPCs and the unlabeled resident endothelial cells. When the EPCs were further modified to express the anti-TDP43 Fab, we could observe integration of these cells into the vasculature and the secretion of Fabs. Results confirm that production and secretion of Fabs at the BBB level leads to their migration to the brain parenchyma where they might exert a therapeutic effect.